Indirect indicators of bovine welfare in the municipality of Loma Bonita, Oaxaca, Mexico - Martínez Castro, César Julio (2022)
The aim of this study was to determine the indirect management indicators that can negatively influence the welfare of cattle in the municipality of Loma Bonita, Oaxaca, Mexico. A survey with 20 indirect indicators (items) was applied between December 2019 to March 2020 to 27 farmers with a focus on milk production. The sampling was non-probabilistic for convenience. An exploratory factor analysis was used as a statistical technique for data analysis. Of the 20 indicators, 14 were present because there are producers who do not carry out certain practices, or the management is incorrect or deficient. The factor analysis grouped them into five factors that explained 76.34% of the accumulated variance. These were: 1) Dehorning management; 2) Milking management; 3) Preventive health management; 4) Calving management and 5) Herding and preventive miking management, where the first two were the ones with the highest contribution with 24.4 and 14.4%, respectively. It is concluded that through technical advice and training it is possible to raise awareness and support these producers to improve daily and eventual management activities in which they have weaknesses.